2016
DOI: 10.1530/erp-16-0022
|View full text |Cite
|
Sign up to set email alerts
|

Global longitudinal strain: a useful everyday measurement?

Abstract: Herceptin (Trastuzumab) is a widely used and effective drug for the treatment of Her2+ breast cancer but its cardiotoxic side effects require regular monitoring by echocardiography. A 10% reduction in left ventricular ejection fraction can lead to suspension of treatment and therefore has significant implications for patient prognosis in terms of cardiac and cancer outcomes. Assessment of LV function by conventional 2D biplane method of discs (2DEF) has limitations in accuracy and reproducibility. Global longi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…Given the median follow-up time in the current study of 7 years, the interval may be too short for the development of a decreased LVEF of <54%. Because of the limitations in sensitivity and reproducibility of the LVEF, we decided to also use the GLS of the LV which is a more sensitive method to detect subclinical systolic dysfunction of the LV 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Given the median follow-up time in the current study of 7 years, the interval may be too short for the development of a decreased LVEF of <54%. Because of the limitations in sensitivity and reproducibility of the LVEF, we decided to also use the GLS of the LV which is a more sensitive method to detect subclinical systolic dysfunction of the LV 25 .…”
Section: Discussionmentioning
confidence: 99%
“…In case of GLS, breast cancer studies, including those on trastuzumab, showed that a relative reduction of 2–15% from baseline GLS was associated with increased rate of cardiotoxicity, and accordingly, reductions > 15% from baseline in GLS have been suggested for detection of LV dysfunction by most experts' consensus statements. 15) 86) 114) 115) 116) 117) …”
Section: Prevention Of Cardiovascular Toxicitymentioning
confidence: 99%
“…It has been proposed that the left ventricle global longitudinal strain (LV‐GLS) could be a useful tool for the detection of early systolic dysfunction in patients under cardiotoxic chemotherapy (Thavendiranathan et al , ). Moreover, the high reproducibility of the LV‐GLS represents an advantage over the left ventricle ejection fraction (LVEF) (King et al , ; Medvedofsky et al , ). Compared to the LVEF, the LV‐GLS is less affected by changes in loading conditions, which makes it a potentially useful tool in patients with sickle cell disease (SCD), due to the chronic overload associated with SCD.…”
Section: Univariate Analysis Results Show Differences Between Scd Andmentioning
confidence: 99%